The sensitivity test of vibrio cholerae from isolation of diarrhea case to various type of antibiotics - Khariri Khariri; Novi Amalia; Sundari Nursofiah; Fauzul Muna; Yuni Rukminiati (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2020)
One of the microbes that causes acute diarrhea is bacteria. Vibrio cholerae is one that causes diarrhea called cholera diarrhea. Cholera diarrhea is caused by enterotoxins produced by these bacterial colonies in the small intestine. Giving antibiotics is still the main choice in the treatment and treatment of diarrhea because it is expected to kill bacteria and will usually stop diarrhea. Irrational use and the existence of abuse and excessive use of antibiotics can be a factor that causes bacterial resistance to antibiotics. Tests carried out to determine the sensitivity of bacteria to an antibiotic. Vibrio cholerae isolate was regrowed in alkaline peptone (APW) water medium and incubated at 37ºC for 18-24 hours, then planted in the thiosulfate-citrate-bile-sucrose (TCBS) medium. The sensitivity test was carried out on V. cholerae bacterial colonies growing on TCBS agar medium with the Disk Diffusion Method from Kirby Bauer. Data were analyzed descriptively. The results showed that most V. cholerae isolates were still sensitive to all types of antibiotics used in the test. Vibrio cholerae has shown resistance to Colistin antibiotics that is equal to 88.2%, Ampicillin at 23.5% and Ceftazidime at 5.9%. The level of resistance to antibiotics that are still low indicates that the antibacterial group can still be used as an alternative in the treatment of cholera diarrhea.